2002
DOI: 10.1063/1.1473669
|View full text |Cite
|
Sign up to set email alerts
|

A two-dimensional nonlinear photonic crystal for strong second harmonic generation

Abstract: Articles you may be interested inEnhancement of second harmonic generation in NaNO2-infiltrated opal photonic crystal using structural light focusing Appl. Phys. Lett. 105, 051902 (2014); 10.1063/1.4892363Effects of shapes and orientations of reversed domains on the conversion efficiency of second harmonic wave in two-dimensional nonlinear photonic crystals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…SHG has been investigated using an FDTD scheme in one-dimensional bulk structures and stratified media [27][28][29][30] and in two-dimensional defective photonic crystals [18][19][20]. Recently, a two-dimensional FDTD code has been proposed for the study of both second-and third-order nonlinear phenomena [31].…”
Section: Fdtd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…SHG has been investigated using an FDTD scheme in one-dimensional bulk structures and stratified media [27][28][29][30] and in two-dimensional defective photonic crystals [18][19][20]. Recently, a two-dimensional FDTD code has been proposed for the study of both second-and third-order nonlinear phenomena [31].…”
Section: Fdtd Analysismentioning
confidence: 99%
“…In Raineri et al [18] the SHG is observed in a linear defect realized by removing an entire row of air holes in a two-dimensional triangular lattice of AlGaAs; the pump field at the FF and the generated SH fields become confined in the PC waveguide and they also interact under the phase-matching condition. An infinite array of square rods of LiNbO 3 surrounded by air is presented in Shi et al [19]. The defects in this structure are introduced by changing the side length of some rods in the PC so that a transmittance peak, which refers to a defect mode, appears in the band gap.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown (by a standard method of harmonic expansion) that for a particular photonic crystal (PC) of square symmetry there are wavelengths at which such flattening occurs in particular spatial directions in certain propagation band [2][3][4][5]. On the other hand the PCs can be made in nonlinear materials and thus they can be used in nonlinear optics, in particular for observation of the efficient SHG [6][7]. More recently, it has been suggested also that both χ (3) [8] and χ (2) [9] nonlinear processes can be considerably increased using PC structures tuned to subdiffractive regimes.…”
Section: Introductionmentioning
confidence: 99%
“…The linear defect is able to confine the pump field at fundamental wavelength (FW) and the generated SH field and the wavelength conversion efficiency relies on phase-matching condition. An infinite array of square rods of LiNbO 3 surrounded by air was proposed in (Shi et al 2002) where, periodically changing the side length of some rods, defects are introduced in the PC which allow the rise of resonant modes in the band gap. The fundamental field is trapped near the defect, being the fundamental wave tuned to the defect mode wavelength: SHG efficiency enhances since the localized field intensity becomes higher than the incident light one.…”
Section: Introductionmentioning
confidence: 99%